Theoretical Basis of Management of Detection and Regulation of Tax Violations in Business Entities - Anvarjon Makhmudov (American Journal of Economics and Business Management, 2025)
This document presents the primary findings of scientific study about the development and enhancement of the tax system in our nation, as well as studies focused on preventing and rectifying tax infractions within the context of the ongoing priority economic reforms. The underlying causes of taxpayer evasion and tax avoidance influenced by infractions are examined comprehensively. The necessity to implement efficient procedures to prevent scenarios that diminish the economic impact of infractions, particularly with tax system management, and to provide a systematic approach for the use of these mechanisms is evident.